STUDENTS’ PERCEPTION TOWARDS NATIONAL EXAMINATION: COMPUTER-BASED TEST OR PAPER-BASED TEST - Sumiati Sumiati (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2018)
AbstractToday, technological development has given a new lease of life in language learning and teaching field. Particularly in terms of evaluation, some schools in Indonesia conduct national examination using computer-based test. Traditionally, testing in a class involves paper-based test which is familiar to students. A substantial number of studies have been conducted to compare both of the tests. The researcher investigated what activities were performed by the students throughout the tests, what kind of multiple choice tests the students prefer to do, and what the positive and negative side of those tests. This study presents a wonder share quiz creator (WSQC) program to facilitate the teachers to design a test. The data was collected by questionnaire, interview, observation, and quiz. In this study, the authors concluded that students in senior high school of Yaspih Rajeg prefer paper-based test for national examination.Keywords: computer-based test, National Examination, paper-based test AbstrakSaat ini, perkembangan teknologi memberikan perubahan dalam dunia pengajaran dan pembelajaran bahasa. Khususnya dalam hal evaluasi, beberapa sekolah di Indonesia melakukan ujian nasional menggunakan tes berbasis komputer. Secara tradisional, pengujian di kelas melibatkan tes berbasis kertas yang akrab bagi siswa. Sejumlah besar studi telah dilakukan untuk membandingkan kedua tes. Peneliti menyelidiki kegiatan apa yang dilakukan oleh siswa selama tes, jenis tes pilihan ganda apa yang siswa sukai, dan apa sisi positif dan negatif dari tes tersebut. Penelitian ini menyajikan a wonder share quiz creator (WSQC) untuk memfasilitasi para guru untuk merancang tes. Data dikumpulkan dengan kuesioner, wawancara, observasi, dan kuis. Dalam penelitian ini, penulis menyimpulkan bahwa siswa di SMA Yaspih Rajeg lebih suka ujian berbasis kertas untuk ujian nasional. Kata kunci: tes berbasis komputer, Ujian Nasional, tes berbasis kertas